FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Seika Carol; Jonnardi Jonnardi (Jurnal Paradigma Akuntansi, 2023)
The purpose of this research is to examine the influence of profitability, firm size and liquidity to capital structure on manufacture company that registered on Indonesia Stock Exchange in period of 2016-2020. Then based on simple random sampling that used in this research This research is conducted by using 49 company industry that registered on Indonesia Stock Exchange as sample have been discovered. The data source of the research is the secondary data obtained not direct. Data analysis was performed with descriptive statistics. The results of this research shows that profitability had a positive and significant effect to capital structure companies, firm size had no siginifcant to capital structure, and liquidity had a negative and significant effect to capital strcuture companies.